Android-Based Educational Model Cross Puzzle to Improve Dental Health Behavior among Elementary Schools - Nurizza, Efa; Santoso, Bedjo; Rasipin, Rasipin; Marsum, Marsum; Wiyatini, Tri (International Journal of Nursing and Health Services (IJNHS), 2022)
Background: Dental health problems in the intervention group primary school were dental caries at 81%, persistence at 32%, gingivitis at 35%, and dental health problems in the control group primary school namely dental caries at 86%, persistence at 36%, gingivitis 48%. Dental health problems in elementary school children are caused by low dental health maintenance behavior. The strategy to overcome this problem is by using an "Android-based crossword puzzle education model" providing education to children through the game method so that the learning process is more interesting and fun. Design: This research design uses the Research and Development method Quasi-experimental with a pre-test-post-test control group design. Result: The treatment in the intervention group and control group was given for 21 days. The Android-based crossword puzzle education model according to expert validation is an average of 92% and a p-value of 0.002 (very feasible) and its application is effective as an effort to improve dental health behavior in elementary school children, as well as a different test of crossword puzzle education models android-based effective as an effort to increase knowledge of delta p-value 0.009, attitude delta p-value 0.001, delta p-value 0.001 action, debris index score delta p-value 0.001 compared to the control group. Conclusion: The Android-based crossword puzzle education model is feasible, and its application is effective as an effort to improve dental health behavior in elementary school children compared to the control group Keywords: Elementary school children, behavior, dental health, crossword puzzle educational model